Long-Term Vestibular Outcomes in Cochlear Implant Recipients - Rasmussen, Kasper Møller Boje; West, Niels; Tian, Luchen; Cayé-Thomasen, Per (Frontiers in Neurology, 2021)
Background: Vestibular dysfunction is likely the most common complication to cochlear implantation (CI) and may, in rare cases, result in persistent severe vertigo. Literature on long-term vestibular outcomes is scarce. Objective: This paper aims to evaluate vestibular dysfunction before and after cochlear implantation, the long-term vestibular outcomes, and follows up on previous findings of 35 consecutive adult cochlear implantations evaluated by a battery of vestibular tests. Methods: A prospective observational longitudinal cohort study was conducted on 35 CI recipients implanted between 2018 and 2019; last follow-up was conducted in 2021. At the CI work-up (T0) and two postoperative follow-ups (T1 and T2), 4 and 14 months following implantation, respectively, all patients had their vestibular function evaluated. Evaluation with a vestibular test battery, involving video head impulse test (vHIT), cervical vestibular evoked myogenic potentials (cVEMP), caloric irrigation test, and dizziness handicap inventory (DHI), were performed at all evaluations. Results: vHIT testing showed that 3 of 35 ears had abnormal vHIT gain preoperatively, which increased insignificantly to 4 of 35 at the last follow-up (p = 0.651). The mean gain in implanted ears decreased insignificantly from 0.93 to 0.89 (p = 0.164) from T0 to T2. Preoperatively, 3 CI ears had correction saccades, which increased to 11 at T2 (p = 0.017). Mean unilateral weakness increased from 19 to 40% from T0 to T2 (p < 0.005), and the total number of patients with either hypofunctioning or areflexic semicircular canals increased significantly from 7 to 17 (p < 0.005). Twenty-nine percent of CI ears showed cVEMP responses at T0, which decreased to 14% (p = 0.148) at T2. DHI total mean scores increased slightly from 10.9 to 12.8 from T0 to T1 and remained at 13.0 at T2 (p = 0.368). DHI scores worsened in 6 of 27 patients and improved in 4 of 27 subjects from T0 to T2. Conclusion: This study reports significant deterioration in vestibular function 14 months after cochlear implantation, in a wide range of vestibular tests. vHIT, caloric irrigation, and cVEMP all measured an overall worsening of vestibular function at short-term postoperative follow-up. No significant deterioration or improvement was measured at the last postoperative follow-up; thus, vestibular outcomes reached a plateau. Despite vestibular dysfunction, most of the patients report less or unchanged vestibular symptoms.